Drug prescription in elderly hospitalized patients with cognitive impairment in the Italian dementia‐friendly hospital project: Developing topics. (7th December 2020) - Govoni, Stefano; Rosi, Alessia; Preda, Stefania; Allegri, Nicola
Abstract: Background: Older patients with cognitive impairment represent a significant proportion of the patients hospitalized for various acute illnesses. The health staff is not prepared to deal with such patients which do not fit the standard of care of the hospital stay. Accordingly, we recorded a series of clinical parameters reflecting the health status and the drug prescriptions at the entry and during hospital stay before and after a brief (5 hrs. frontal teaching) intervention of staff training, focusing on improving the management of patients with cognitive impairment. Methods: Participants were evaluated within 48 h of admission and at discharge with Mini Mental State Examination (MMSE), Barthel Index, Instrumental Activity of Daily Life (IADL), and Hospital Anxiety and Depression Scale (HADS). A preliminary analysis of 68 hospitalized participants aged 65 and older with cognitive impairment (MMSE ≥ 16, ≤24) allocated in the control group (n = 34, 20 females, 82.38 years) and intervention group (n = 34, 20 females, 81.97 years) was performed. For each patient, the number of prescriptions, sedative and anticholinergic load, and drug–drug interactions were evaluated. Results: Participants presented a widespread polypharmacy receiving as average 6.9 (+/‐ 1.7 drugs/daily in the control group) and 5.9 (+/‐ 1.6 drugs/daily in the intervention group), the difference being not statistically significant (P = 0, 068). Also, the sedative load presented a trend toward lower values in the intervention group. The results concerning the other clinical indices (submitted elsewhere) show that personnel training significantly improved the functional and anxiety parameters at discharge. Conclusions: The results suggest that an intervention, focused on improving dementia care practices in health staff, having the potential to improve outcomes for hospitalized older adults with cognitive impairment, but not directly designed to manage drug polypharmacy, is not sufficient to modify drug prescription patterns.